Iryna Ivakhnenko. Vasyl’ Danylevych's contribution to the development of museum work in Ukraine - Ivakhnenko, Iryna (Young Scholars Grinchenko – Seton International Journal, 2021)
Abstract. The article is devoted to the personality of the famous Ukrainian historian, scientist, public figure, archaeologist, numismatist, museologist Vasyl’ Danylevyh. The relevance of the study consists in researching the museum activities of the Ukrainian historian at the end of the 19th – in the first third of the 20th century. Vasyl’ Danylevych was born in a family of a hereditary nobleman, graduated from the 4th Kyiv gymnasium and the History and Philology Faculty of St. Volodymyr University in Kyiv. Under the guidance of Professor Volodymyr Antonovych he wrote a competitive work “An Outline of the History of the Polotsk Land until the end of the XIV century” for which he received a gold medal and the right to become a professorial scholarship holder and continue his studies in the master's program. He became a member of the Kyiv School of Historians of Professor Antonovych. Vasyl’ Danylevych took an active part in the work of several Ukrainian museums. He worked in the Museum of Fine Arts and Antiquities at Kharkov University, in the Ethnographic Museum of Historical and Philological Society of Kharkiv University. In Kyiv he participated in the work of the Kyiv Art, Industrial and Scientific Museum and the Museum of Antiquities of the St. Volodymyr University. He also founded the Archaeological Museum of Higher Women's Courses in Kyiv. In these museums he headed certain departments, carried out energetic activities for the development of these institutions, replenished attached to museums the collections of libraries and the collections of coins, various finds, and created their lists, etc. Vasyl’ Danylevych managed to draw attention to the museum works and museum activities of his students, and then the museums were replenished with new archaeological materials collected by him and students. During more than 40 years of scientific and more than 30 years of teaching activities, Vasyl’ Danylevych proved himself in various fields. His research interests covered a wide range of issues related to the history and archeology of Kyivan Rus’, numismatics, historical geography and other issues. From the memoirs of his student, the scientist took a very thorough and critical approach to his work, so his accuracy in work allowed him to clearly express himself and make a significant contribution not only in the field of museum work, but also in his scientific activities in general. Keywords: Vasyl` Danylevych, historian, scientist, museologist, museum activity, St. Volodymyr University, Professor Antonovych Kyiv School of Historains, Kharkiv University, the Museum of Antiquities of St. Volodymyr University, the Ethnographic Museum of Historical and Philological Society of Kharkiv University, Kyiv Art-Industrial and Scientific Museum, Kyiv Higher Women's Courses Archaeological Museum, the end of the 19th – the first third of the 20th century, St. Volodymyr University, Kharkiv University, Kyiv.